Pengaruh Inflasi dan Tingkat Pengangguran terhadap Pertumbuhan Ekonomi di Indonesia - Multhazam, Riana (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Economic growth is a crucial indicator of development performance, yet it is often influenced by macroeconomic conditions such as inflation and unemployment. This study aims to examine the effect of inflation and unemployment on economic growth in Indonesia. The research employs a quantitative approach using a time series design and multiple linear regression analysis. Secondary data were obtained from Statistics Indonesia and Bank Indonesia for the period 2015–2023. The results reveal that inflation has a negative and significant effect on economic growth, while unemployment also shows a negative and significant impact. Simultaneously, inflation and unemployment significantly influence Indonesia’s economic growth. These findings highlight the importance of price stability and effective labor absorption in supporting sustainable economic growth. Therefore, integrated economic policies are required to control inflation while simultaneously expanding productive employment opportunities.